Stochastic Modeling and Optimization of Laser Machining by Response Surface Methodology - Sivarao, Subramonian; Ammar, Abd Rahman; T., Joseph Sahaya Anand; Salleh, Mohd Shukor (IJENS Publishers, 2010)
Design of experiment uses a series of structured analytic method to investigate the relation between parameters and the responses. The particular technique used in this study is response surface methodology. Using the DOE approach, a mathematical based model was developed through regression analysis to study the response prediction. It is found that for kerf width the cutting speed plays an important role. Only a high cutting speed can produce good kerf width. When considering the interaction between the parameters, duty cycle directly depends on frequency where a high duty cycle is needed for high frequency cutting and vice versa to obtain a good kerf width.